A Complete Constellation of Nervous System Lesions of NF2: Imaging Evaluation. (11th March 2012) - Gangadhar, Kiran; Kumar, Sandeep; Bhatia, Lovekesh; Agarwal, Arjit
Abstract : The radiological findings fulfilling the criteria of neurofibromatosis type 2 (NF2) were reviewed. NF2 is a rare disease with few cutaneous but frequent, typical radiological findings in the central nervous system. The presenting symptom is most commonly hearing loss due to acoustic schwannomas, although symptoms emanating from other intracranial or tumors are not uncommon. The discovery of multiple spinal neurofibromas or multiple meningiomas without cutaneous lesions should initiate a search for acoustic schwannomas even when the patient has normal hearing as in our case patient who actually presented for weakness of all four limbs.